Exploring the home advantage and home winning effect in handball: Differences between sexes and team level - Marquina Nieto, M.; García-Sánchez, C.; Nieto-Acevedo, R.; de la Rubia, A. (International Journal of Sports Science & Coaching, 2025)
The aim of the study was to analyse and compare the extent of home advantage (HA) and home winning percentage (HW) by sex and team classification in Spanish First Division handball leagues. Results data were collected from the first divisions of the Spanish men's and women's handball leagues for 10 seasons (2013-2024), excluding the season by COVID19. For each team in each season, the variables of HA (%) determined as (total home points / total points) * 100 and HW (%) calculated as (total home wins / total home games) * 100 were found. In addition, teams were divided into high (HLT), medium (MLT) and low (LLT) level teams based on the percentage of games won in each season using cluster analysis. Males had higher HA values than females (p < 0.05), however, there was no difference in HW (p > 0.05). In addition, males had higher HA values than females separately in MLT and LLT (p < 0.05) and higher HW values only in the LLT (p < 0.001). LLT had higher HA than MLT and HLT (p < 0.001), while HLT had higher HW than MLT and LLT (p < 0.001). Thus there are differences in HA and HW by sex and team level. Male teams experienced greater HA and HW effects, suggesting that female teams have a more even distribution of wins in home and away games. In addition, LLT seem to rely more on home games to achieve wins, while HLT seem to be more successful both at home and away.